Assessing the Impact of Economic Solar Energy Systems on Regional Development in Nigeria and Africa - Rao, P. Nageswara; Bal, Yakubu Barau; Danladi, Muhammad Nazif (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study presents the design and analysis of a 5 kW solar tree system tailored for residential applications in Bauchi State, Nigeria, offering a cost-effective and space-efficient renewable energy solution. Aimed at meeting a daily energy demand of 30,000 Wh, the system is optimized based on the region’s solar irradiance levels. The design incorporates essential components, including photovoltaic (PV) modules, a charge controller, a battery bank, an inverter, and a structurally robust steel support framework. Performance evaluations indicate an operational efficiency exceeding 86% and annual electricity cost savings of approximately $1,415. Structural validation using engineering analysis yields a safety factor of 2.85, confirming the system's resilience to wind loads and environmental stresses. The study underscores the potential of solar tree systems to reduce reliance on fossil fuels and contribute to Nigeria’s broader transition toward sustainable energy infrastructure.